The determinants of saving behaviour in Malaysia / Mohd Hafiz Husin - Husin, Mohd Hafiz (Faculty of Business and Management, 2008)
This study was conducted to examine the determinants of saving behaviour in the process of economic development, in the light of the Malaysian experience during the period 1974-2006. The long-debated relationship between savings and the level and growth rate of income has provided a strong motivation for analyzing the determinants of saving behaviour in Malaysia. The methodology involves the estimation of a saving rate function derived within the life cycle framework while paying attention to the structural characteristics of a developing economy. It is found that the saving rate rises with both the level and the rate of growth of income. Among the other variables considered, deposit interest rate, demographic variables and current account balance as statistically significant positive influences on domestic saving and inflation rate and old dependency ratio have negative impact on domestic saving.